Analysing the relationship between dividend policy and macroeconomic variables with firm's performance: A case of consumer product companies in Malaysia - Muhammad Izham bin Mohd Fauzi (Universiti Tenaga Nasional, 2023)
HG4028.D5 .M83 2015